Phenolic Compound, Triterpene and Steroids From The Leaves and Bark of Dysoxylum Macrocarpum - Najmuldeen, Ibrahim A.; Ketuly, Kamal Aziz; Hadi, A. Hamid A. (Science Journal of University of Zakho, 2013)
The bark and leaves of Dysoxylum macrocarpum (Meliaceace) yielded four compounds, two compounds from the leaves; 5-hydroxy-7-methoxy-2-methyl-4H-chromen-4-one (Eugenin) DM1, which was new as crystal and squalene DM2, while two more compounds were found from the bark; stigmasterol DM3 and sitosterol DM4. The present work involves extraction, isolation and purification of compounds by using column chromatography followed by preparative TLC. Structural elucidation has been done through several spectroscopic methods, notably UV, IR, MS (HRMS, GCMS, and LCMS), 1D, 2D-NMR 1H NMR, 13CNMR, COSY, DEPT, HMQC, HMBC, and single crystal X-ray diffraction analysis.